Resposta :
Explicação passo-a-passo:
a) A(2,7) e B(2,4)
xa=2
ya=7
xb=2
yb=4
[tex]d = \sqrt{(xa - xb) {}^{2} + (ya - yb) {}^{2} } [/tex]
[tex]d = \sqrt{(2 - 2) {}^{2} + (7 - 4) {}^{2} } [/tex]
[tex]d = \sqrt{0 {}^{2} + 3 {}^{2} } [/tex]
[tex]d = \sqrt{0 + 9} [/tex]
[tex]d = \sqrt{9} [/tex]
[tex]d = > 3[/tex]
b) A(3,-3) e B(3,5)
xa=3
ya=-3
xb=3
yb=5
[tex]d = \sqrt{(xa - xb) {}^{2} +( ya - yb) {}^{2} } [/tex]
[tex]d = \sqrt{(3 - 3) {}^{2} + ( - 3 - 5) {}^{2} } [/tex]
[tex]d = \sqrt{0 {}^{2} + (-8) {}^{2} } [/tex]
[tex]d = \sqrt{0 + 64} [/tex]
[tex]d = \sqrt{64} [/tex]
[tex]d = > 8[/tex]
c) A(3,4) e B(-2,4)
xa=3
ya=4
xb=-2
yb=4
[tex]d = \sqrt{(xa - xb) {}^{2} + (ya - yb) {}^{2} } [/tex]
[tex]d = \sqrt{(3 + 2) {}^{2} + (4 - 4) {}^{2} } [/tex]
[tex]d = \sqrt{5 {}^{2} + 0 {}^{2} } [/tex]
[tex]d = \sqrt{25 + 0} [/tex]
[tex]d = \sqrt{25} [/tex]
[tex]d = > 5[/tex]
d) A(-4,-2) e B(0,2)
xa=-4
ya=-2
xb=0
yb=2
[tex]d = \sqrt{(xa - xb) {}^{2} + (ya - yb) {}^{2} } [/tex]
[tex]d = \sqrt{( - 4 - 0) {}^{2} + ( - 2 - 2) {}^{2} } [/tex]
[tex]d = \sqrt{( - 4) {}^{2} + (-4) {}^{2} } [/tex]
[tex]d = \sqrt{16 + 16} [/tex]
[tex]d = \sqrt{32} [/tex]